Sistem Pakar Untuk Menentukan Status Pertumbuhan Pada Anak Menggunakan Inferensi Fuzzy (Sugeno) - Emi Agustina; Agus Sidiq Purnomo (Faculty of Computer Science, University of Jember, 2018)
The detection of child growth should be done as early and as accurately as possible, so that if there is a deviation of child growth can be known earlier and can be found a solution to the deviation. In the examination of children who performed in pharmacies depok sleman pengelolahan data inspection done manually so that data is not well recorded, it causes the data is lost and not clear. For that we need a system capable of data menguin so as to minimize the things that are not desirable. In this study, the researchers aimed to create an expert system that gives an idea of the growth in children with fuzzy logic motede which requires several variables, namely age, height, gender and weight which will be taken z-score weight and z- Score height. Based on the test result which has been done with 85 examination data of children, it can be concluded that the implementation of fuzzy sugeno method can be used as a determination of the status of the child's growth with total accuracy of 81.18%.